Aplikasi Majalah Dinding “Wall On” Berbasis Android Jurusan Teknik Elektronika Fakultas Teknik UNP - Putri Maharani; Zulhendra Zulhendra; Dedy Irfan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
The Development of science nowadays develop rapidly furthermore lead make human activity more easily especially in technology and communication. The development in science has made a change how people nowaday get information. Wall magazine is one of media for college student to get some information. Wall magazine for college student not only about lecture activity but also about many information e.g. announcement about loss something, advertisement,event information and etc. This application “WallOn” is designed to help college student to get the latest news or information about campus. This application can reduce paper as a media for news and information. The method used based on UML model object oriented. In the server side using PHP as programming language with MySQL as database management system and Sublime Text as text editor meanwhile in the client side using JAVA as proramming language, JSON and android studio that can run in android. An android base application is designed to obtained an application that can accommodate needed e.g give an information or news, not only in campus area but also out of campus.Keywords: Android Application, Wall Magazine, client-server, php, MySql